2020
DOI: 10.1038/s41380-020-0755-z
|View full text |Cite|
|
Sign up to set email alerts
|

A DNA methylation clock associated with age-related illnesses and mortality is accelerated in men with combat PTSD

Abstract: DNA methylation patterns at specific cytosine-phosphate-guanine (CpG) sites predictably change with age and can be used to derive "epigenetic age", an indicator of biological age, as opposed to merely chronological age. A relatively new estimator, called "DNAm GrimAge", is notable for its superior predictive ability in older populations regarding numerous age-related metrics like time-to-death, time-to-coronary heart disease, and time-to-cancer. PTSD is associated with premature mortality and frequently has co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 41 publications
13
55
0
Order By: Relevance
“…A possible explanation for this finding is that Horvath's method is a multi-tissue calculator trained across multiple non-cancer and cell lines, whereas the other three DNAm age calculators were trained on blood samples. Our study also replicated the findings of the two recent studies which showed that GrimAge age acceleration was significantly associated with PTSD diagnosis 21,22 . GrimAge was constructed based on CpGs associated with smoking and plasma proteins previously found to predict mortality or morbidity, and has been shown to outperform its predecessors in mortality prediction 17 .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…A possible explanation for this finding is that Horvath's method is a multi-tissue calculator trained across multiple non-cancer and cell lines, whereas the other three DNAm age calculators were trained on blood samples. Our study also replicated the findings of the two recent studies which showed that GrimAge age acceleration was significantly associated with PTSD diagnosis 21,22 . GrimAge was constructed based on CpGs associated with smoking and plasma proteins previously found to predict mortality or morbidity, and has been shown to outperform its predecessors in mortality prediction 17 .…”
Section: Discussionsupporting
confidence: 90%
“…GrimAge was constructed based on CpGs associated with smoking and plasma proteins previously found to predict mortality or morbidity, and has been shown to outperform its predecessors in mortality prediction 17 . Taken together, the findings from these three PTSD studies (including the current study) 21,22 suggest that GrimAge is a powerful epigenetic age predictor in PTSD.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…DNA methylation (DNAm) is a cellular process of epigenetic regulation employed by cells to control gene expression without altering the genetic sequence. Commercial epigenome-wide arrays (Illumina series) have been proven to be highly reproducible and yielded the identification of DNAm markers that can be accurate and stable enough to estimate white blood cell composition [13], smoking history [14], and age [15][16][17]. Moreover, there is growing evidence that epigenetic processes play an important role in the etiology of psychological disorders [18] and PTSD [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%